Multi-server identity authentication scheme based on biometric and chaotic maps - Jianwu ZHANG; Zejin YAO; Zhendong WU (Dianxin kexue)
Password-based user remote authentication system has been widely used in recent years,the study found that a single password system is so vulnerable to dictionary analysis and brute force attack as well as other attacks that the security is not high.Biometric and password combination authentication method gradually added to the remote authentication system in order to improve the security level of authentication system.However,the existing authentication systems work in a single server environment,if extended to a multi-server environment,biometric templates and passwords will encounter single point breakthrough and cross-crack problem.In order to overcome the above problems,a multi-server key authentication scheme based on biometric and chaotic map was proposed.The scheme was based on smart cards,passwords and biometrics,which could significantly improve the security and the ability of anti-password guessing of multi-server authentication systems.